2018
DOI: 10.1186/s12955-018-1028-2
|View full text |Cite|
|
Sign up to set email alerts
|

Defining the minimally clinically important difference of the SF-36 physical function subscale for paediatric CFS/ME: triangulation using three different methods

Abstract: BackgroundDefining the minimally clinically important difference (MCID) is important for the design and analysis of clinical trials and ensures that findings are clinically meaningful. Studies in adult populations have investigated the MCID of The Short Form 36 physical function sub-scale (SF-36-PFS). However, to our knowledge no studies have defined the MCID of the SF-36-PFS in a paediatric population. We aimed to triangulate findings from distribution, anchor and qualitative methods to identify the MCID of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 41 publications
1
30
2
Order By: Relevance
“…Compared with the ‘inactive’ class, being in the ‘light’ or ‘active’ class was associated with improved physical function by 10.4 and 15.3 points, respectively, which is greater than the minimal clinically importance difference for the SF36-PFS 23 42 43. There was some evidence to suggest that being in the ‘light’ class was associated with lower levels of fatigue compared with being in the ‘inactive’ class, but adjusting for time since diagnosis attenuated this association.…”
Section: Discussionmentioning
confidence: 90%
“…Compared with the ‘inactive’ class, being in the ‘light’ or ‘active’ class was associated with improved physical function by 10.4 and 15.3 points, respectively, which is greater than the minimal clinically importance difference for the SF36-PFS 23 42 43. There was some evidence to suggest that being in the ‘light’ class was associated with lower levels of fatigue compared with being in the ‘inactive’ class, but adjusting for time since diagnosis attenuated this association.…”
Section: Discussionmentioning
confidence: 90%
“…(this paper) (2) Which outcomes are important for children with CFS/ME and their parents? (paper under review) (3) What is the minimally clinically important difference in fatigue and SF-36 physical function scale?14 Participants and parents/carers were asked about each of these three areas. The answers to our research question on recovery are reported in this paper.…”
Section: Methodsmentioning
confidence: 99%
“…Qualitative patient interviews are an emerging approach to additionally explore score interpretation and contextualize estimates in terms of how a patient feels and functions. 17,18 This study aimed to establish MID and RD for the EORTC QLQ-MY20 utilizing both existing clinical trial data and prospective patient interviews. The aim of this study was thus to recommend MIDs and RDs for each scale of the EORTC QLQ-MY20 for use in MM patients.…”
Section: Introductionmentioning
confidence: 99%
“…Distribution‐based estimates do not directly consider what is meaningful to patients or clinicians, and will vary across samples, impeding consistent interpretation. Qualitative patient interviews are an emerging approach to additionally explore score interpretation and contextualize estimates in terms of how a patient feels and functions …”
Section: Introductionmentioning
confidence: 99%